Psychoanalysis, religion and architecture. Fray Gabriel Chávez de la Mora and the monastery of Santa María de la Resurrección - Esteban Fernández-Cobián (Hispania Sacra)
At the end of the sixties, the Mexican monastery of Santa María de la Resurrección, located in Ahuacatitlán, near Cuernavaca (Mexico), caused rivers of ink to flow due to its novel therapies, in which the Benedictine monks underwent group psychoanalytic processes. The commotion that this entailed, motivated that in 1967, the monastic community decided to dissolve, after its prior, the Belgian priest Gregorio Lemercier, was repeatedly admonished by the Vatican authorities. Starting from the dispersed existing documentation, and abundant unpublished material, this article proposes, in the first place, to reconstruct the events that took place in the monastery of Ahuacatitlán. Secondly, to highlight the architectural implications of the process, something that no one has noticed to date. Finally, to underline the role that Fray Gabriel Chávez de la Mora played as architect of the monastery and, especially, of its circular chapel, very novel and controversial for that time.